Squash : steps to success - Yarrow, Philip , 1968-; Harrison, Aidan , 1971- (Champaign, Illinois : Human Kinetics, 2010)
"With 13 progressive instructional steps, you'll learn all aspects of the game of Squash. Detailed descriptions, illustrations, and photo sequences demonstrate essential on-the-court movement, volleys, serves, returns, and drop shots. Then practice and improve techniques with 93 drills, each featuring a personal scoring system to gauge and accelerate your progress"
1. Proper grip and basic swings -- 2. Court movement -- 3. Moving and hitting in the frontcourt -- 4. Moving and hitting in the backcourt -- 5. Volleys -- 6. Serve and return -- 7. Boasts -- 8. Drop and lob shots -- 9. Kill shots -- 10. Disguise and deception -- 11. Match play -- 12. Advanced tactics -- 13. Conditioning for squash
Keywords: Squash (Game)